Aerosol reduction efficacy of different intra-oral suction devices during ultrasonic scaling and high-speed handpiece use - Krystyna Piela; Paddy Watson; Reuben Donnelly; Marilyn Goulding; Fiona L. Henriquez; William MacKay; Shauna Culshaw (BMC, 2022)
Abstract Background The COVID-19 pandemic led to significant changes in the provision of dental services, aimed at reducing the spread of respiratory pathogens through restrictions on aerosol generating procedures (AGPs). Evaluating the risk that AGPs pose in terms of SARS-CoV-2 transmission is complex, and measuring dental aerosols is challenging. To date, few studies focus on intra-oral suction. This study sought to assess the effectiveness of commonly used intra-oral suction devices on aerosol mitigation. Methods Ultrasonic scaling and high-speed handpiece procedures were undertaken to generate aerosol particles. Multiple particle sensors were positioned near the oral cavity. Sensor data were extracted using single board computers with custom in-house Bash code. Different high-volume and low-volume suction devices, both static and dynamic, were evaluated for their efficacy in preventing particle escape during procedures. Results In all AGPs the use of any suction device tested resulted in a significant reduction in particle counts compared with no suction. Low-volume and static suction devices showed spikes in particle count demonstrating moments where particles were able to escape from the oral cavity. High-volume dynamic suction devices, however, consistently reduced the particle count to background levels, appearing to eliminate particle escape. Conclusions Dynamic high-volume suction devices that follow the path of the aerosol generating device effectively eliminate aerosol particles escaping from the oral cavity, in contrast to static devices which allow periodic escape of aerosol particles. Measuring the risk of SARS-CoV-2 transmission in a dental setting is multi-factorial; however, these data suggest that the appropriate choice of suction equipment may further reduce the risk from AGPs.